The Legal System Nationality Of Legal Person In Private International Law - جامع , شادي; ابراهيم, لوجين (Latakia University Journal - Economic and Legal Sciences Series, 2021)
It is recognized in law the right of a natural person to has a nationality , this is because of his legal personality. Nationality is considered a tool for distributing individuals internationally among states and for distinguishing patriots from foreigners. The law provides legal persons with the power to acquire rights and assume obligations, with an agreement not lo grant it some rights in compatible with its financial entity that is far from loyalty. In our research, we will study the problem of nationality of legal person in light of rules of private international law, the opinion of jurists, and the position of Syrian law.